2021
DOI: 10.3389/fpls.2021.724847
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Informed Breeding Strategies for Strawberry Yield and Fruit Quality Traits

Abstract: Over the last two centuries, breeders have drastically modified the fruit quality of strawberries through artificial selection. However, there remains significant variation in quality across germplasm with scope for further improvements to be made. We reported extensive phenotyping of fruit quality and yield traits in a multi-parental strawberry population to allow genomic prediction and quantitative trait nucleotide (QTN) identification, thereby enabling the description of genetic architecture to inform the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 57 publications
4
19
0
Order By: Relevance
“…Despite the extensive improvement of strawberries in recent years, there is still a large variation in fruit quality, both within and among cultivars, due to the influence of environmental factors and adopted production systems [51,52]. Prat et al [46] reported improvements in the organoleptic quality of fruits in soilless cropping systems.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive improvement of strawberries in recent years, there is still a large variation in fruit quality, both within and among cultivars, due to the influence of environmental factors and adopted production systems [51,52]. Prat et al [46] reported improvements in the organoleptic quality of fruits in soilless cropping systems.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of improving these traits including breeding, by exploiting the potential of crop wild relatives as a source of new traits, and/or the genetic manipulation/genome editing of specific traits. There is already evidence that substantial genetic variation exists within wild relatives of fruiting crops [ 100–102 ], which are now studied as a source of crop improvement in various breeding programs [ 103 ]. Further evidence that even in elite material, significant variation is observed in photosynthetic traits.…”
Section: Impact Of Elevated [Co 2 ] On Yield and Q...mentioning
confidence: 99%
“…It is widely distributed in the Northern Hemisphere being present across Eurasia and Eastern North America (Hilmarsson et al., 2017), and is a rich, but untapped, resource for genetic and metabolic diversity relevant to strawberry breeding programs. The shape and size of strawberry fruit (more technically, the fleshy receptacle) are under hormonal control and the genetic basis underlying these traits as well as quality traits influencing flavor and aroma have begun to be unraveled (Cockerton et al., 2021).…”
Section: Figurementioning
confidence: 99%